APPLICATION OF OCCLUSAL SPLINTS IN THE DIGITAL ERA: A SERIES OF THREE CASE REPORTS - Lenka Vavrickova; Jan Schmidt; Hana Hubalkova; Doriana Agop Forna; Martin Kapitan (Romanian Journal of Oral Rehabilitation)
This manuscript presents three case reports demonstrating the use of occlusal splints fabricated through both conventional and digital methods in clinical practice. The first case involves a 65-year-old male bruxist treated with a 3D-printed Muscle Relaxation Appliance to alleviate muscular facial pain and restore vertical dimension occlusion. The second case describes a 30-year-old pregnant woman with anterior disc displacement without reduction (DDwoR) who received an Anterior Repositioning Appliance fabricated using additive digital technology to improve temporomandibular joint function. The third case features a 70-year-old male undergoing implant-supported full-mouth reconstruction, utilizing a conventionally made splint for centric relation to achieve a stable horizontal relationship between the maxilla and mandible. These cases highlight the practical application of digital facebow technology and CAD/CAM workflows in enhancing the precision and comfort of occlusal splint therapy. The results emphasize the effectiveness of customized splint designs in managing complex temporomandibular disorders and related orofacial conditions.